The Arctic Council. Governance for environmental protection in the Arctic - Hervör Pálsdóttir 1980- (2018)
The Arctic is changing at a rate unprecedented in history. The Arctic has a dynamic relationship with the rest of the world, both nature and humans. Known and unknown factors interact with each other to magnify the changes happening and the environment, the peoples of the Arctic and the rest of the world face great changes and challenges. As the Arctic is an area under several jurisdictions and legal systems the Arctic Council Member States need to find a way to cooperate to protect their individual and common interests, as well as the global interests involved, to fulfil their obligations. The forum for this cooperation has been the Arctic Council from 1996. The Arctic Council has worked towards the protection of the Arctic and the common interests of its Member States, on issues connected to the Arctic. The Arctic Council has been extremely focused on environmental protection and has developed into a forum for these obligations to be addresses as well as for the states to further their interests in the Arctic by asserting management and governance control. Thus, the positive action by the Arctic states through the Arctic Council is both beneficial to the respective states as well as for the environment as a whole. The Arctic Council Member States seem to be asserting more policy goals to the management of the Arctic and there is a common voice for the strengthening of the Arctic Council.